Irrigation indicators of Mukhrani meadow soils - Olga Kharaishvili; Nana Parulava; Tamar Akhaladze; Irma Iremashvili (World Scientific Reports, 2023)
Mukhran-Saguramo valley is an erosion plain, which was formed by the material brought by the rivers Ksani, Aragvi, Narekvavi and many other rivers and streams in the form of pebbles and gravel. Clay soils are mainly distributed on the Narekvavi river catchment area, and pebbly and stony soils on the rest of areas. The surface of entire area is almost covered with alluvial material rich in carbonates, thickness of which reaches 3-6 m. The following types of soil are common on the territory of the study field: alluvial, brown and meadow brown, mountain-meadow soils and their various subtypes. Most of the agricultural crops are spread on alluvial and meadow brown soils. All types of alluvial-carbonate soils are common in Shida Kartli, among which the largest area is spreaded by muddy soils. According to the content of nutrients, they are fertile soils, but they are characterized by structurelessness and unsatisfactory hydrophysical properties. Brown meadow soils are also widespread in the mentioned zone, which are located mainly in the elevated, foothill and mountainous areas of the valley.